Disaster diplomacy in Jammu and Kashmir. (October 2018) - Kelman, Ilan; Field, Jessica; Suri, Kavita; Bhat, Ghulam M.
Abstract: Disaster diplomacy investigates how and why disaster-related activities do and do not influence conflict and cooperation. Studies into the topic so far have tended to develop the theory, analyse a specific case study in space and time, or connect both. Explorations of disaster diplomacy case studies over the long-term are so far absent from the literature. This paper explores Jammu and Kashmir in the Himalaya as a long-term case study for disaster diplomacy. Jammu and Kashmir has a long history of conflicts, multiple environmental hazards, and significant vulnerabilities yielding major disasters, with each topic generally addressed separately in the literature. This paper explores the intersection of vulnerabilities to environmental hazards and violent conflict for Jammu and Kashmir throughout its history. The analysis validates and refines previous disaster diplomacy conclusions. First, violent conflicts in Jammu and Kashmir cannot be shown to be either created or ended by environmental hazard incidences. Second, when vulnerabilities create disasters from environmental hazards, then short-term influences on violent conflict are sometimes seen, but these influences are not witnessed over a long time period.